Structural patterns in William Faulkner's major novels - Quammen, D (1972)
William Faulkner wrote nineteen novels. Continually experimenting with the structure of the narrative, he produced a few superbly successful technical achievements, an intermediate body of works that are fascinating for what they attempt and the ways they attempt it, and more than several outright failures. With an experimenter, even a failure is usually of some interest. "(I)t was simply because to me that seemed the most effective way to tell that story,"! Faulkner would answer to questions about his use of a particular unorthodox structure. But in spite of that disavowal, and in spite of the fact that it is undoubtedly true, that the novels were certainly first and foremost independent units, with structures selected as purely as possible to present most effectively the given story and theme; still, there are connections to be made among the various novels. At least eight of the major works, in fact, are built on the pattern of two types of structure, which might be given the labels contrapuntal and centripetal. "To what extent does Faulkner work in terms of polarities, oppositions, paradoxes, inversions of roles?" Robert Penn Warren asked, reviewing Malcolm Cowley's compilation of The Portable Faulkner, in August, 1946. "How much does he employ a line of concealed (or open) dialectic progression as a principle for his fiction? The study of these questions may lead to the discovery of principles of organization in his work not yet defined by criticism."! Such a study has yet to be systematically done. Continued in thesis ...